The Importance Of Trust In Oscar Wilde's An Ideal Husband (1895): A Sociological Approach - Azuni, Putri Churatul (2012)
The purpose of this study is describing the life style in the late nineteenth century focus on Victorian society. The object of this study is one of play written by Oscar Wilde An Ideal Husband, and it takes setting in London. In this opportunity this studies applying the qualitative method. There is relationship between this play and social condition in that time. The theoretical approach using sociological approach is appropriate with the main idea of Oscar Wilde. The data sources are collected from the internet and sociological books includes the play itself, biography of the author, sociological condition, structural elements of play, and are the data analyzed by descriptive analysis. The result of the study it can be seen in this following conclusion: (1) The purpose of the author of this play is to criticize the social reality in that time using the structural elements of play; (2) this play is written during the England's in industrial revolution; and (3) this play tell for us about the reality social in the late nineteenth century England, conduct with Hypocrisy, social status and damaged of trust.